The new European Union space policy in order to maintain Europe's position among space leaders - Piotr Kolczyński (CES Working Papers, 2018)
This paper analyzes the current EU space strategy and confronts it with nowadays global challenges in the space sector. The ultimate aim of it is to recommend a well-adjusted space policy for the European Commission for assuring effective and sustainable exploration and use of outer space for the benefit of all EU members. In order to craft the most efficient space policy, the uniqueness of Europe's space sector is studied. This paper argues that the EU space policy has to focus on guaranteeing European autonomy in access and use of outer space. It also aims to extensively analyze the challenges and opportunities related to dynamic development of private space sector's activities. It emphasizes the significance of symbiotic cooperation between public institutions and private companies with regard to mutual benefits. The paper concludes that it is a right time for the European Union to build a bold and prospective space policy.
Keywords: 330; European space policy; space law; European autonomy; ESA and EU; Private space sector